2020
DOI: 10.1155/2020/9625798
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation Site Affects the Outcomes of Adipose-Derived Stem Cell-Based Therapy for Retinal Degeneration

Abstract: Adipose-derived stem cells (ASCs) have shown a strong protective effect on retinal degenerative diseases (RDD) after being transplanted into the subretinal space in an animal model. Recently, several clinical trials have been conducted to treat RDD with intravitreal transplantation of stem cells, including ASCs. However, the outcomes of the clinical trials were not satisfactory. To investigate if the transplantation site alters the outcome of stem cell-based therapy for RDD, we isolated rat ASCs (rASCs) and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
(58 reference statements)
2
12
0
1
Order By: Relevance
“…As shown in Figures 1 , 2 , transplanted MSCs EPO formed a sheet of cells that adhered to the retina, which resulted in the thickening of the tissue. This was commonly observed in other rodent studies that have employed the intravitreal route of MSC transplantation ( Labrador Velandia et al, 2018 ; Hu et al, 2020 ). Those studies showed that MSCs mostly remain in the vitreous space and may form membranes rather than penetrate the inner retinal layers.…”
Section: Discussionsupporting
confidence: 66%
“…As shown in Figures 1 , 2 , transplanted MSCs EPO formed a sheet of cells that adhered to the retina, which resulted in the thickening of the tissue. This was commonly observed in other rodent studies that have employed the intravitreal route of MSC transplantation ( Labrador Velandia et al, 2018 ; Hu et al, 2020 ). Those studies showed that MSCs mostly remain in the vitreous space and may form membranes rather than penetrate the inner retinal layers.…”
Section: Discussionsupporting
confidence: 66%
“…As shown in Figures 1, 2, transplanted MSCs EPO formed a sheet of cells that adhered to the retina, which resulted in the thickening of the tissue. This was commonly observed in other rodent studies that have employed the intravitreal route of MSC transplantation (Labrador Velandia et al, 2018;Hu et al, 2020). Those studies showed that MSCs mostly remain in the vitreous space and may form membranes rather than penetrate the inner retinal layers.…”
Section: Discussionsupporting
confidence: 57%
“…However, MSCs pretreated by alpha-aminoadipic acid may improve the structural integration of vitreous transplanted cells [38] . In addition, some researchers have found that transplantation of MSCs into the subretinal space is a more effective route than the vitreous chamber [36,39] . In addition, some clinical trials have used suprachoroidal application [40] and tenon delivery [41] .…”
Section: Discussionmentioning
confidence: 99%